Management of a Maxillary Radicular Cyst in a Patient with Gilbert Syndrome: A Rare Case Report (Academia Journal of Medicine, 2024)
Gilbert syndrome is a rare benign autosomal genetic  disorder characterized by reduced activity of glucuronyl  transferase, leading to decreased clearance of bilirubin  and occasional mild jaundice in the absence of hepatic  injury or hemolysis. Diagnosis involves clinical and  laboratory investigations as part of differential diagnosis,  with genetic analysis providing additional confirmation.  Oral manifestations of Gilbert syndrome exist but often go  unnoticed. Drugs metabolized by this enzyme need to be  considered along with stress management in patients  undergoing surgical procedures. This case report of a 24- year-old male diagnosed with a radicular cyst in the  maxillary anterior teeth region, who incidentally exhibited  Gilbert syndrome, also highlights perioperative  management considerations for such patients.
Keywords: Gilbert syndrome; Radicular cyst; Perioperative management